Pengembangan Perangkat Pembelajaran Quantum Teaching Pada Materi Ajar Elastisitas - Rusyadi, Ahmad; Zainuddin, Zainuddin; Wati, Mustika (Universitas Lambung Mangkurat, 2013)
The low of student learning outcomes in learning physics, because learning process tense, students interest to learning in science is low yet. It is necessary for research that aims to describe the effectiveness of the quantum teaching-learning development to improving student learning outcomes. The aim, in particular, are described: (1) the feasibility of the device, (2) implemented RPP, (3) student activities, (4) student learning outcomes, and (5) the students interest. Learning refers to the development using of Dick & Carey model. Data collection techniques used observation, achievement test, and questionnaire. Data obtained by descriptive qualitative and quantitative. The results showed: (1) a device in the effective category to be used, (2) implemented RPP at a meeting I, II, III are goods category, (3) each meeting student activity are increased in the excellent category, (4) increase every classical completeness meeting with percentages respectively 71.18%, 81.25% and 84.37%, (5) the students interest towards learning well categorized. The retrieved conclusion that the effectiveness of the quantum teaching-learning teaching materials elasticity in the effective category.Â